STRATEGI PEMILIHAN GAYA KEPEMIMPINAN DALAM PENGUATAN TATA KELOLA LEMBAGA PENDIDIKAN ISLAM - Iqbal Ramdhani; Siska Septia Ulfa; Khaidarul Amjad; Muhammad Sirozi (LP2M IAIN Sultan Amai Gorontalo, 2026)
The governance of Islamic educational institutions relies heavily on the effectiveness of leadership applied by institutional leaders. One of the most critical aspects of leadership practice is the ability to select an appropriate leadership style that aligns with institutional needs, the characteristics of human resources, and the Islamic values underpinning education. This article aims to analyze strategies for selecting leadership styles that strengthen governance in Islamic educational institutions. This study employed a library research method with a descriptive qualitative approach. Data were collected from books, national and international journals, and relevant academic documents. The findings revealed that selecting a leadership style requires careful consideration of institutional characteristics, internal and external dynamics, organizational culture, and Islamic spiritual values. Prophetic leadership, Islamic transformational leadership, and participatory leadership based on syura are the most suitable styles for Islamic educational institutions because they strengthen governance, encourage collaboration, and promote a quality-oriented organizational culture. This article presents several strategic recommendations for leaders of Islamic educational institutions in selecting effective leadership styles, including institutional needs analysis, reflection on Islamic values, human resource empowerment, and routine evaluation of leadership implementation. Thus, this study offers theoretical and practical contributions to strengthening governance in Islamic educational institutions through effective and Islamic leadership practices.